# How do you solve #4x+5y=-23# and #x= -2-5y# using substitution?

Multiply out the bracket

Add 23 to both sides

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the system of equations ( 4x + 5y = -23 ) and ( x = -2 - 5y ) using substitution, you can substitute the expression for ( x ) from the second equation into the first equation and solve for ( y ). Then, substitute the value of ( y ) back into either equation to find the value of ( x ).

First, substitute ( x = -2 - 5y ) into ( 4x + 5y = -23 ):

[ 4(-2 - 5y) + 5y = -23 ] [ -8 - 20y + 5y = -23 ] [ -15y = -15 ] [ y = 1 ]

Now, substitute ( y = 1 ) back into ( x = -2 - 5y ):

[ x = -2 - 5(1) ] [ x = -2 - 5 ] [ x = -7 ]

So, the solution to the system of equations is ( x = -7 ) and ( y = 1 ).

By signing up, you agree to our Terms of Service and Privacy Policy

- How do solve the following linear system?: # 9 x-6y =3 , x + y= 12 #?
- How do solve the following linear system?: # -6x+5y=1 , 6x+4y=-1 #?
- How do you solve the system #9a+2b=10# and #9a-2b=10#?
- How do you solve the following system using substitution?: #5x+2y=-4, -3x+y=20#
- Why is matrix multiplication not commutative?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7